PENGARUH LATIHAN AGILITY LADDER DRILL TERHADAP PENINGKATAN KELINCAHAN PEMAIN DI SSB PUTRA PAGERSARI U 13-15 - Muhammad Iqbal Mahardika; Agus Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of agility ladder drill training on improving the agility of football players aged 13-15 years at SSB Putra Pagersari. The method used was quantitative experimental with a One Group Pre-test - Post-test design. The research subjects consisted of 13 players. Data were collected through measurement of agility before and after the training treatment. The results of data analysis using normality, homogeneity, and paired sample t-test showed that the data were normally distributed, homogeneous, and there was a significant difference between the pre-test and post-test results (Sig. 0.000 < 0.05; t-value 44.832 > t-table 2.26). All participants experienced an increase in agility, indicated by a decrease in completion time ranging from 1.24 to 2.40 seconds. The agility ladder drill proved effective e for physical training programs to develop agility, speed, movement coordination, and motor response in young players. It is recommended that football coaches at the SSB level implement this training more regularly in a systematic and structured manner. Furthermore, incorporating varied drills and conducting periodic evaluations are essential to maintain and optimize training outcomes in the long term.